2018
DOI: 10.1002/path.5058
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genome integration in squamous carcinogenesis: what have next‐generation sequencing studies taught us?

Abstract: Human papillomavirus (HPV) infection is associated with ∼5% of all human cancers, including a range of squamous cell carcinomas. Persistent infection by high-risk HPVs (HRHPVs) is associated with the integration of virus genomes (which are usually stably maintained as extrachromosomal episomes) into host chromosomes. Although HRHPV integration rates differ across human sites of infection, this process appears to be an important event in HPV-associated neoplastic progression, leading to deregulation of virus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 60 publications
(179 reference statements)
9
52
0
Order By: Relevance
“…Other HPV transcripts (E2, E4, E5, E8 and L2) were not detected in all the cell lines. These HPV genome profiling results were consistent with previous reports 36,37 .…”
Section: Resultssupporting
confidence: 93%
“…Other HPV transcripts (E2, E4, E5, E8 and L2) were not detected in all the cell lines. These HPV genome profiling results were consistent with previous reports 36,37 .…”
Section: Resultssupporting
confidence: 93%
“…2D, >10 TPY or T4 disease). By analyzing matched tumor genomics, we discovered that patients with low pretreatment ctHPV16DNA levels ( 200 copies/mL) had lower tumor HPV copy number and a higher likelihood of HPV integration, which are associated with worse outcomes in OPSCC (5,6,(8)(9)(10)(11)(12)29). In contrast, patients with abundant pretreatment ctHPV16DNA levels (>200 copies/mL plasma) were most likely to have tumors with high copy and episomal HPV, which correlates with favorable prognosis in both cervical cancer and OPSCC (8,9,11,14).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the frequency of single or multiple infections according to the lesion grade, we found that the prevalence of single infections was more elevated in low-grade lesions, which can indicate a dissipation effect of a determined genotype to achieve the integration of its genome to the host’s; while the exact mechanisms by which high-risk HPV genotypes succeed in the integration of their genome aren’t completely understood, it has been reported that with the development of next-generation sequencing it is possible to determine the exact integration site and the subsequent genomic rearrangements to it. It has been indicated that such phenomenon takes place through two main mechanisms, loop integration and direct integration, and that a better understanding of the integration sites might allow to understand those factors that give a competitive advantage to certain genotypes during the progression of the disease [29]. However, in our patients with high-grade lesions a synergic effect with even three different genotypes seems to happen, probably as a result of the expression of a higher viral load and even though conflict exists whether if the viral load size or the integration status are determinant factors for the development of high-grade lesions, in a study performed by Manawapat-Klopfer et al with 664 Danish women it was demonstrated that a 10-fold increase of the viral load, in addition to a state of viral genome integration, was significantly associated to the presence of a high-grade lesion [30].…”
Section: Discussionmentioning
confidence: 99%